SIMULASI ANALISIS GANGGUAN SISTEM KELISTRIKAN SULSELRABAR MENGGUNAKAN POWERWORLD SIMULATOR - Ratih puspita siwi (Jurnal Pendidikan Teknik Elektro Undiksha, 2024)
The South Sulawesi Electricity System consists of 51 buses with the highest peak load at 19.00 WITA of 1073.9 MW. The number of buses being simulated consists of 41 buses because the maximum number in the PowerWorld Simulator software only reaches 41 buses. In the simulated PowerWorld Simulator program, the Bakaru Bus with a working voltage of 150 kV is assumed to be the reference bus. The simulation results show that for faults that occur on each bus, the largest fault current is 10892,400 A, namely when a 3-phase fault occurs on Bus 5 Sungguminasa smallest fault current is 9433,090 A, namely when it occurs on Bus 5 (Sungguminasa Bus). Meanwhile, the largest instantaneous voltage value lies in the Line to Line fault type, namely Bus 2 (Bontoala Bus) with a disturbance value of 1.01179 kV with a working voltage of 149.07 kV after the disturbance occurs and the smallest instantaneous voltage occurs in the Single Line to Ground fault type, namely Bus 22( Sidera bus) with a disturbance value of 0.95961 kV, working voltage 70.83 kV after a disturbance occurs.